Development of a digital pocket based on mind mapping to improve learning outcomes - Adena Nurasiah Siregar; Daulat Saragi; Anita Yus (Himpunan Pengembang Kurikulum Indonesia, 2026)
This research discusses the development of a digital pocket book based on mind mapping on class IV mutual cooperation material. The research aims to describe the level of feasibility, practicality and effectiveness of mind mapping-based digital pocket books to improve student learning outcomes in class IV Pancasila Education subjects. This study employed a research and development (RnD) approach, applying the ADDIE model. The study was conducted at Sabilina Private Elementary School, Percut Sei Tuan District, Deli Serdang Regency, North Sumatra. The subjects were all 30 fourth-grade students in the 2023/2024 academic year. The results of the study indicate that the developed mind-mapping-based digital pocketbook was deemed excellent, valid, and suitable for use, based on assessments by subject matter experts, media experts, and language experts. The use of this digital pocketbook has proven effective in improving student learning outcomes in Pancasila Education. Furthermore, the mind-mapping-based digital pocketbook also demonstrated excellent practicality and received positive responses from teachers and students, making it suitable for use as a learning medium in elementary schools. Abstrak Penelitian ini membahas tentang perkembangan buku saku digital berbasis mind mapping pada materi gotong royong kelas IV. Penelitian bertujuan untuk mendeskripsikan tingkat kelayakan, kepraktisan dan keefektifan buku saku digital berbasis mind mapping untuk meningkatkan hasil belajar siswa pada mata pelajaran Pendidikan Pancasila kelas IV. Penelitian ini menggunakan pendekatan penelitian dan pengembangan (Research and Development) dengan menerapkan model ADDIE. Penelitian dilaksanakan di SD Swasta Sabilina, Kecamatan Percut Sei Tuan, Kabupaten Deli Serdang, Sumatera Utara. Subjek penelitian adalah seluruh siswa kelas IV tahun ajaran 2023/2024 yang berjumlah 30 orang. Hasil penelitian menunjukkan bahwa buku saku digital berbasis mind mapping yang dikembangkan dinyatakan sangat baik, valid, dan layak digunakan berdasarkan penilaian ahli materi, ahli media, dan ahli bahasa. Penggunaan buku saku digital ini terbukti efektif dalam meningkatkan hasil belajar siswa pada pembelajaran Pendidikan Pancasila. Selain itu, buku saku digital berbasis mind mapping juga menunjukkan tingkat kepraktisan yang sangat baik serta mendapatkan respons positif dari guru dan siswa, sehingga sesuai digunakan sebagai media pembelajaran di sekolah dasar. Kata Kunci: buku saku digital; hasil belajar; mind mapping.